2019
DOI: 10.1021/acsomega.9b00755
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor Adsorption–Desorption Behavior of Surfactant-Coated Starch Particles for Commercial Energy Wheels

Abstract: This study reports on the adsorption (dehumidification)–desorption (humidification) behavior of cetylpyridinium bromide (CPB) coated starch particles (SPs), denoted as SP-CPB, as a potential desiccant material for air-to-air energy exchangers. CPB is a cationic surfactant with antibacterial activity that can be used to modify the surface properties of SPs, especially at variable CPB loading levels (SP-CPB0.5, SP-CPB2.5, and SP-CPB5.0, where the numeric suffix represents the synthetic loading level of CPB in mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…Despite the differences in molecular-level properties of N 2 and H 2 O (size and dipolar character) adsorptive probes, the N 2 BET results provide estimates of the textural properties of FFs versus SPs. By contrast, results obtained for the water vapor isotherms reveal differences because of its adsorbate size, adhesive interactions, and capillary effects, as evidenced by the contrasting results reported for the SPs . The textural properties of the biodesiccants in the present study are further supported by the single-step change and cyclic test results, according to differences in the rate of adsorption/desorption for FFs versus SPs.…”
Section: Resultssupporting
confidence: 77%
“…Despite the differences in molecular-level properties of N 2 and H 2 O (size and dipolar character) adsorptive probes, the N 2 BET results provide estimates of the textural properties of FFs versus SPs. By contrast, results obtained for the water vapor isotherms reveal differences because of its adsorbate size, adhesive interactions, and capillary effects, as evidenced by the contrasting results reported for the SPs . The textural properties of the biodesiccants in the present study are further supported by the single-step change and cyclic test results, according to differences in the rate of adsorption/desorption for FFs versus SPs.…”
Section: Resultssupporting
confidence: 77%
“…We have demonstrated that controlled surface patterning of starch particles yields composite materials with tunable physicochemical properties that are understood according to Sabatier’s principle on the basis of optimal CPB surface adsorption onto SPs. Such surfactant-modified SPs are envisaged to be suitable for advanced applications that require switchable adsorption properties with improved stability/longevity and functional versatility as sustainable carrier systems and desiccant coatings in energy wheels . Sustainability, eco-efficiency, and cost are guiding the next generation of materials with applications in the environment, biomedicine, and energy. …”
Section: Discussionmentioning
confidence: 99%
“…Such surfactant-modified SPs are envisaged to be suitable for advanced applications that require switchable adsorption properties with improved stability/longevity and functional versatility as sustainable carrier systems and desiccant coatings in energy wheels . Sustainability, eco-efficiency, and cost are guiding the next generation of materials with applications in the environment, biomedicine, and energy. …”
Section: Discussionmentioning
confidence: 99%
“…The space heating and cooling of commercial, residential, and industrial buildings are responsible for 30-50% of energy consumption and greenhouse gas emissions in Canada [4] and EU [5]. Space heating, cooling, and ventilation of buildings are the main tasks of Heating, Ventilating, and Air Conditioning (HVAC) systems and account for 60% and 54% of the energy consumption by residential and commercial buildings, respectively [6]. Thus, It is estimated that HVAC systems make up 15-30% of global energy consumption [6].…”
Section: Introductionmentioning
confidence: 99%
“…Space heating, cooling, and ventilation of buildings are the main tasks of Heating, Ventilating, and Air Conditioning (HVAC) systems and account for 60% and 54% of the energy consumption by residential and commercial buildings, respectively [6]. Thus, It is estimated that HVAC systems make up 15-30% of global energy consumption [6].…”
Section: Introductionmentioning
confidence: 99%